2019
DOI: 10.1177/1753425919839125
|View full text |Cite
|
Sign up to set email alerts
|

The synovial fluid neuropeptide PACAP may act as a protective factor during disease progression of primary knee osteoarthritis and is increased following hyaluronic acid injection

Abstract: The correlation of serum and synovial fluid (SF) pituitary adenylate cyclase-activating polypeptide (PACAP) levels with disease progression of primary knee osteoarthritis (OA) was explored. Radiographic severity of OA was determined by Kellgren–Lawrence (K-L) grades. PACAP levels were measured by ELISA before treatment, and 4 and 8 wk following hyaluronic acid (HA) injection. Levels of IL-1β and MMP-3 were also detected. The numeric pain scale (NPS), revised Oxford Knee Score (OKS), and American Knee Society S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 46 publications
(54 reference statements)
0
11
0
Order By: Relevance
“…Bay-Jensen reported that serum COL3/ADAMTS was weakly associated with pain scores (r=-0.13-0.17, p<0.05) (44). Sun compared MMP-3 and NRS but did not find any correlation (45). Moreover, no other associations between SF catabolic proteases and pain have been found, except for the above-mentioned results.…”
Section: Discussionmentioning
confidence: 78%
“…Bay-Jensen reported that serum COL3/ADAMTS was weakly associated with pain scores (r=-0.13-0.17, p<0.05) (44). Sun compared MMP-3 and NRS but did not find any correlation (45). Moreover, no other associations between SF catabolic proteases and pain have been found, except for the above-mentioned results.…”
Section: Discussionmentioning
confidence: 78%
“…Bay-Jensen reported that serum COL3/ ADAMTS was weakly associated with pain scores (r = − 0.13-0.17, p < 0.05) [44]. Sun compared MMP-3 and NRS but did not find any correlation [45]. Moreover, no other associations between SF catabolic proteases and pain have been found, except for the above-mentioned results.…”
Section: Discussionmentioning
confidence: 85%
“…Bay-Jensen reported that serum COL3/ADAMTS was weakly associated with pain scores (r=-0.13-0.17, p<0.05) (44). Sun compared MMP-3 and NRS but did not found any correlations (45). No other correlations between SF catabolic proteases and pain were found in a previous study except for the above-mentioned results.…”
Section: Discussionmentioning
confidence: 58%